Pengaruh Dukungan Sosial, Religiusitas dan Strategi Koping Terhadap Ketahanan Keluarga di Desa Sagaranten Wilayah Kerja Puskesmas Sagaranten Kabupaten Sukabumi - Dedi Wahyudin (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2022)
One of the factors that determine the quality of a nation and state is the family. In the current era of globalization, a family will always be confronted with a variety of challenges and conflicts; if they are unable to respond to these situations, their resilience may be compromised. Several markers, including social support, religiosity, and family-owned coping methods, can influence family resilience. This study intends to examine the impact of social support, religiosity, and coping methods on the resilience of families.This is a correlational study using a cross-sectional design. The sample consists of 299 individuals out of a population of 1184 using a cluster random sampling technique. Data retrieval via surveys and statistical analysis included descriptive data analysis of respondent characteristics, as well as simple and multiple linear regression analysis. The results showed that social support affected family resilience (b=1.717, p=0.000), religiosity affected family resilience (b=2.105, p=0.000) and coping strategies affected family resilience (b=0.708, p=0.000). Social support, religiosity and coping strategies have a simultaneous effect on family resilience (p=0.000). The finding indicates that social support, religiosity, and coping methods have a simultaneous effect on family resilience in Sagaranten Village, the Working Area of the Sagaranten Health Center in Sukabumi Province.